2004
DOI: 10.1111/j.1365-3180.2004.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing variability in fecundity of Amaranthus powellii using a simulation model

Abstract: Summary Estimates of weed fecundity and its variability are critical for the development of population dynamic models and for evaluating the long‐term consequences of weed management practices. The purpose of this research was to estimate Amaranthus powellii fecundity across years, seasons and competitive environments using a mechanistic model. Existing models were modified to account for weed responses to shade, and to dynamically simulate seed production among subthreshold densities of A. powellii. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…For example, in 1997, weed biomass at the time of corn harvest in FC + CL treatments was 153 g m 22 , compared to only 4.4 g m 22 in FC treatments. Since Amaranthus species accounted for at least half of this dry weight, and reproductive effort among Amaranthus species can easily exceed 300 seeds g 21 (Brainard and Bellinder 2004), weed seed input in FC + CL treatments may have exceeded that of FC treatments by 20,000 seeds m 22 or more in 1997. However, this effect clearly did not occur in every year, since no difference in weed seedbank in these two treatments was observed in cycle 2 ( Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 1997, weed biomass at the time of corn harvest in FC + CL treatments was 153 g m 22 , compared to only 4.4 g m 22 in FC treatments. Since Amaranthus species accounted for at least half of this dry weight, and reproductive effort among Amaranthus species can easily exceed 300 seeds g 21 (Brainard and Bellinder 2004), weed seed input in FC + CL treatments may have exceeded that of FC treatments by 20,000 seeds m 22 or more in 1997. However, this effect clearly did not occur in every year, since no difference in weed seedbank in these two treatments was observed in cycle 2 ( Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…However, this effect clearly did not occur in every year, since no difference in weed seedbank in these two treatments was observed in cycle 2 ( Figure 2B). Large year to year variation in seed production in identically managed systems is not unusual due to variation in weed fecundity or efficacy of weed management practices in response to weather conditions (Brainard and Bellinder 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A simulation study assessing variability in Powell amaranth fecundity suggested that seed production occurs in relatively few high seed production environments, and seeds produced from those high-fecundity years have critical influence on the characteristics of the Powell amaranth seed bank (Brainard and Bellinder 2004). Given the much higher seed production reported (Wu and Owen 2014) and high levels of dormancy we observed in the current study, waterhemp seeds from 2010 cohorts are more likely to become part of the persistent soil seed bank than those produced in 2009, and thus will be more of a concern to farmers with regard to long-term waterhemp management.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, growers need a very high degree of biological understanding to control weeds at the economic threshold (Coble 1994). New models are addressing the issue of herbicide-resistant weeds and seed production from a multiyear perspective, with more emphasis on managing weed seed production (Brainard and Bellinder 2004;Doyle and Stypa 2004).…”
Section: Managing Herbicide Use In Herbicide-resistant Cropsmentioning
confidence: 99%